MANUFACTURING CAPABILITIES AND THE LEVELS OF THE MOLD CORES QUALITY MANAGEMENT - I. N. Prusenko (Литьë и металлургия)
The possibilities of the management of the original material properties in themold core blend, the processes of molding sand preparation, shaping and the conditions of technological preparation of mold cores for shaping high quality defect-free internal surfaces of the castings with required geometric relationship, dimensional accuracy and the surface roughness are considered.